(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تتأثر العملية التعليمية في الجامعات بالعديد من العوامل المادية والبشرية والإدارية, وإن تحديد مدى تأثير كل من هذه العوامل في العملية التعليمية بحيث تعكس كفاءتها , تعتبر عملية صعبة للغاية. ومن اجل تحقيق مستويات متميزة في مخرجات التعليم العالي, لابد من الوقوف عند مستوى كفاءة العملية التعليمية والأداء في الجامعات, لأنها تتأثر بالعديد من العوامل المادية والبشرية والإدارية، مما دعانا إلى استنباط أسلوب كمي لتقييم وقياس كفاءة العملية التعليمية والأداء في المقررات الدراسية الجامعية من خلال تركيب نسب النجاح المختلفة، وكذلك من خلال اختبار نسبة النجاح الخاصة في المقرر, ومن النتائج التي تم الحصول عليها: 1 ـ استنباط علاقة رياضية لقياس كفاءة العملية التعليمية والأداء من خلال تركيب نسبة المتقدمين ونسبة النجاح العامة ونسبة النجاح الخاصة في المقرر i . 2. استنباط علاقة رياضية لقياس كفاءة العملية التعليمية والأداء في المقررات من خلال اختبار نسبة النجاح الخاصة في المقرر i . 3.إن الأزمة التي تمر بها البلاد قد انعكست بشكل كبير وسلبي على كفاءة العملية التعليمية والأداء في المقررات الدرسية في السنوات المختلفة وبحسب الأقسام العلمية. The educational process at universities affected many of the physical ,human and administrative factors ,and to determine the extent of the impact of each of these factors in the educational process to reflect the efficiency, It is considered a very difficult process .In order to achieve output of higher education , we have to stand at the level of the educational process efficiency and performance in universities, because it is affected by many of the physical , human and administrative factors . which invited us to devise a quantitative method for evaluating and measuring the educational process efficiency and performance in school undergraduate courses. By arranging different success rates, as well as through special test success rates in the decision, and the results that were obtained: 1-Devise mathematical relationship to measure the educational process efficiency and performance through the installation of the proportion of applicants and the proportion of the general success and the success rate for in decision. 2-Devise mathematical relationship to measure the educational process efficiency and performance in courses through the test of the success rate for in decision. 3-The crisis experienced by the country has reversed dramatically and negatively educational process efficiency and performance in courses in different years, and according to the scientific departments.